Konstruksi Identitas Diri Remaja di Media Sosial: Analisis Konsep Dramaturgi Erving Goffman - Inosensius Enryco Mokos; Salehudin (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This article analyzes in depth how adolescents actively construct and present their multiple identities on popular social media platforms such as Instagram and TikTok. The analytical approach uses Erving Goffman’s dramaturgy theoretical framework, which views social interaction as a performance. This study specifically explores how the key concepts of “front stage” and “back stage” operate in the digital ecosystem, and highlights the crucial role of “impression management” in adolescents’ attempts to strategically present themselves. Using a comprehensive literature review approach, this article first dissects Goffman’s dramaturgy theory and its relevant core concepts in detail. Next, this theory is integrated with findings from recent studies published between 2019 and 2025, which specifically apply Goffman’s perspective to adolescents’ digital communication behavior and identity construction issues. The analysis shows that social media fundamentally functions as a complex dramaturgical arena. Here, adolescents, both consciously and unconsciously, present “performances” of identity that have been carefully tailored to specific audiences and changing digital contexts. This phenomenon often blurs the boundaries between real identity and constructed representation, creating an interesting dynamic in the formation of adolescent self in the digital era.